1979
DOI: 10.1002/1097-0142(197908)44:2<671::aid-cncr2820440238>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of estrogen receptors in primary breast cancer

Abstract: The estrogen receptor status in 335 primary breast carcinomas was correlated with disease-free interval, survival and site of recurrent disease. Estrogen receptor positive carcinomas had a longer disease-free interval, a longer survival (mastectomy-death) and a longer time interval between recurrence and death. These parameters were also influenced by the lymph node status at mastectomy. Estrogen receptor positive cancers had a significantly better chance of survival independent of lymph node status. Estrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
54
1
4

Year Published

1980
1980
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(66 citation statements)
references
References 2 publications
7
54
1
4
Order By: Relevance
“…Response to therapy has been reported to correlate significantly with both oestrogen receptor (ER) status (Blamey et al, 1980;Jensen, 1981;Stewart et al, 1982;Williams et al, 1986) and progesterone receptor (PgR) status (Stewart et al, 1982;McGuire, 1978;Johnson et al, 1983). Survival from commencing endocrine therapy has also been reported to correlate significantly with ER status (Hahnel et al, 1979;Stewart et al, 1981;Kinne et al, 1981;Paterson et al, 1982;Howat et al, 1985;Williams et al, 1987) and PgR status (Howat et al, 1985;Howell et al, 1984) of the primary tumour.…”
mentioning
confidence: 99%
“…Response to therapy has been reported to correlate significantly with both oestrogen receptor (ER) status (Blamey et al, 1980;Jensen, 1981;Stewart et al, 1982;Williams et al, 1986) and progesterone receptor (PgR) status (Stewart et al, 1982;McGuire, 1978;Johnson et al, 1983). Survival from commencing endocrine therapy has also been reported to correlate significantly with ER status (Hahnel et al, 1979;Stewart et al, 1981;Kinne et al, 1981;Paterson et al, 1982;Howat et al, 1985;Williams et al, 1987) and PgR status (Howat et al, 1985;Howell et al, 1984) of the primary tumour.…”
mentioning
confidence: 99%
“…14 -16 In addition, lymph node metastasis, considered to be the most important prognostic factor in breast cancer, does not alter these findings. 17,18 However, the ER expression is gradually lost during tumor progression, leading to a more undifferentiated state. 19 The majority of ER ϩ tumors are diploid, well differentiated, more common in postmenopausal women and less aggressive than ER Ϫ breast tumors.…”
mentioning
confidence: 99%
“…Intralaboratory variation in a number of studies using LBA is reported to range from 15% to 34% (Hawkins et al, 1975(Hawkins et al, , 1987bTaylor et al, 1982; Davis et al, 1984;Bojar, 1986;Anderson et al, 1989 Nicholson et al, 1986) and 3.7% to 16.7% (Bojar, 1986;Jordan et al, 1986;Leclerq et al, 1986;Nicholson et al, 1986) respectively. The interlaboratory CV for EIA was reported to range between 10% and 19% (Bojar, 1986;Leclerq et al, 1986).ER and the natural history of breast cancer Many studies have reported no correlation between ER status and axillary lymph node status (Maynard et al, 1978;Hahnel et al, 1979;Mason et al, 1983;Williams et al, 1987;Hawkins et al, 1987a). Nevertheless, it has been assumed that ER-negative cells have more metastatic potential.…”
mentioning
confidence: 99%
“…ER and the natural history of breast cancer Many studies have reported no correlation between ER status and axillary lymph node status (Maynard et al, 1978;Hahnel et al, 1979;Mason et al, 1983;Williams et al, 1987;Hawkins et al, 1987a). Nevertheless, it has been assumed that ER-negative cells have more metastatic potential.…”
mentioning
confidence: 99%
See 1 more Smart Citation